(untitled) (Research, Society and Development, 2020)
Objective: describe the experience of working in a diagnostic testing center for Covid-19, from the perspective of nursing professionals. Method: experience report on conducting material collection for Reverse Transcriptase - Polymerase Chain Reaction testing to detect Covid-19. The experience took place from March to May 2020, at a federal public university, in the state of Rio de Janeiro, Brazil. Results: are presented from two sections: Service Flow at the Diagnostic Testing Center and; Perceptions and confrontations while working at the Diagnostic Testing Center. Conclusion: experience has shown that it is a challenge to be at the forefront in the fight against coronavirus due to the risk related to the activity, the scarcity of personal protective equipment and the high demand for work. But, it is possible for nurses, even in this context, to use basic care tools, apply the nursing process and interact with the patient.